Thermal Stress in Outdoor Spaces During Mediterranean Heatwaves: A PET and UTCI Analysis of Different Demographics - Tousi Evgenia; Athina Mela; Areti Tseliou (Urban Science)
Urban public space comfort is essential for improving quality of life, particularly as climate change affects outdoor thermal environments. This study utilizes ENVI-met, a 3D microclimate simulation tool, to assess thermal comfort concerning demographic factors such as age and gender. The findings indicate significant disparities in thermal stress vulnerability among demographic groups. On the hottest day of July 2023, at 10 a.m., children’s PET values were approximately 2 °C higher than those of other groups. By 3 p.m., females experienced slightly higher upper-range thermal stress than males. Elderly individuals aged 80 exhibited a broad range of PET values, from 38.14 °C to 62.39 °C, with prevailing values above 56.9 °C, indicating greater vulnerability to extreme heat. Children aged 8 showed PET values ranging from 40.20 °C to 59.34 °C, with prevailing estimates between 54.2 °C and 55.7 °C. Minimum PET values for children were significantly higher than those for adults, suggesting a greater baseline level of thermal stress. Despite cooling effects in the evening, children remained exposed to more pronounced stress than elderly individuals, males, and females. The UTCI values recorded indicate a period of extreme heat stress for all demographic groups assessed. While individuals aged 35 may encounter considerable discomfort, the severity of the impact is notably more pronounced for both older adults and children. This study underscores the need for tailored management strategies and advocates for expanding ENVI-met’s capabilities to enhance urban resilience and well-being amid rising temperatures.